Shrine devoted to Lord Hanuman - Mumbai Archive Project Team (Jio Institute, 2024)
The oldest surviving structure in the village is Worli Fort, which has a shrine devoted to Lord Hanuman. Overlooking Mahim Bay, this small fort served as a watchtower against piracy, which was rife in the Arabian Sea from the sixteenth century to the eighteenth century.